Understanding the dynamics of the obesity transition in Colombia : analysis by socioeconomic level, age and gender using co-flow structures associated with physical activity, sedentary lifestyle, and consumption of ultra-processed foods (2020)
The prevalence of obesity is shifting towards lower socioeconomic status populations, especially in low- and middle-income countries. To understand the dynamics of obesity and its nutritional transition, we propose a system dynamics model with a conservative coflow structure to evaluate the Colombian urban population's behavior at different levels and health behavior attributes (physical activity (PA), sedentary activities (ST), and consumption of ultra-processed foods (CUPF)). The results show that the burden of obesity is shifting towards the lower SES populations, particularly in lower SES women aged 20-59 years at national level as the GDP increase, also a persistent trend of not compliance at the different attributes specially in ST recommendations. The results at different levels of segregation show heterogeneity specially at the regional level, however those are intent as a tool for decision makers to develop more efficient and customized strategies according to the specific stage of obesity burden.